The Implementation and Evaluation of Health Promotion Services and Programs to Improve Cultural Competency: A Systematic Scoping Review - Jongen, Crystal Sky; McCalman, Janya; Bainbridge, Roxanne Gwendalyn (Frontiers in Public Health, 2017)
Background: Cultural competency is a multifaceted intervention approach which needs to be implemented at various levels of healthcare systems to improve quality of care for culturally and ethnically diverse populations. One level of healthcare where cultural competency is required is in the provision of health promotion services and programs targeted to diverse patient groups who experience healthcare and health inequalities. To inform the implementation and evaluation of health promotion programs and services to improve cultural competency, research must assess both intervention strategies and intervention outcomes. Methods: This scoping review was completed as part of a larger systematic literature search conducted on evaluations of cultural competence interventions in health care in Canada, the United States, Australia and New Zealand. Seventeen peer-reviewed databases, 13 websites and clearinghouses, and 11 literature reviews were searched. Overall, 64 studies on cultural competency interventions were found, with 22 being health promotion programs and services. A process of thematic analysis was utilized to identify key intervention strategies and outcomes reported in the literature. Results: The review identified three overarching strategies utilised in health promotion services and programs to improve cultural competency: community focused strategies, culturally focused strategies, and language focused strategies. Studies took different approaches to delivering culturally competent health interventions; with the majority incorporating multiple strategies from each overarching category. There were various intermediate healthcare and health outcomes reported across the included studies. Most commonly reported were positive reports of patient satisfaction, patient/participant service access and program/study retention rates. The health outcome results indicate positive potential of health promotion services and programs to improve cultural competency to impact cardiovascular disease and mental health outcomes. However, due to measurement and study quality issues, it is difficult to determine the extent of the impacts. Discussion: Examined together, these intervention strategies and outcomes provide a framework which can be used by service providers and researchers in the implementation and evaluation of health promotion services and programs to improve cultural competency. While there is evidence indicating the effectiveness of such health promotion interventions in improving intermediate and health outcomes, further attention is needed to issues of measurement and study quality.